Hemoglobin (Hb) Values Correlated with Fatigue in Patients Undergoing Hemodialysis - Rahmawati, Ima; Windartik, Emyk (STIKes Patria Husada Blitar, 2025)
Kidney damage can reduce the production of erythropoietin, a hormone that stimulates the formation of red blood cells in the bone marrow. This leads to anemia due to a lack of red blood cells. One of the signs of anemia symptoms in chronic kidney disease that has undergone hemodialysis is fatigue. The type of the study was correlation analytic which aimed to analyze the correlation of hemoglobin values with fatigue in patients undergoing hemodialysis with a cross-sectional approach. The population in this study was all patients undergoing hemodialysis in the HD room of RSI Siti Hajar as many as 108 patients. A sample of 40 respondents was taken using a consecutive sampling technique for 4 days. The research instrument used the FAS (Fatigue Assessment Scale) questionnaire and laboratory examination results—data analysis using the Spearman rho correlation test. The results showed that p values of 0.031 < α 0.05 proved a correlation between hemoglobin values and fatigue levels in hemodialysis patients in the HD room of RSI Siti Hajar Sidoarjo. The correlation coefficient (r) of 0.341 indicated a positive correlation with a fairly strong and unidirectional level of correlation strength. The lower the hemoglobin level, the more fatigue patients tend to experience. Therefore it is very important to maintain Hb levels to prevent further decline and reduce fatigue as a result.